2017
DOI: 10.1016/j.aquaculture.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of lipid metabolism, digestibility and antioxidant status of Atlantic bluefin tuna (T. thynnus L.) larvae during first feeding

Abstract: Atlantic bluefin tuna (Thunnus thynnus L.; ABT) larvae were fed on enriched rotifers Brachionus rotundiformis and copepod nauplii Acartia tonsa from first feeding to 15 days post hatching. Rotifers were enriched with five different commercial products: OG, MG, AG and RA plus selenium and vitamin E. Copepods (COP) were cultured with the algae Rhodomonas baltica. Metabolic processes were studied by determining the expression of 30 genes related to lipid metabolism (transcription factors, fatty acid metabolism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
4
7
1
Order By: Relevance
“…In red sea bream, both feeding conditions and dietary lipid and fatty acid levels were shown to alter lpl expression in liver, with lower expression in fish fed low lipid than in fish fed high lipid (Liang et al 2002a ). In the present study, the expression of lpl in liver of ABT juveniles was low and showed no clear response to diet, similar to previous studies where ABT larvae fed different live prey showed variable lpl expression (Betancor et al 2017a , b ). In contrast, hmgcl expression was upregulated in ABT juveniles fed higher lipid (20KO), while previous studies in larvae did not show any dietary regulation of this gene (Betancor et al 2017a , b ) although increased expression of this enzyme has been associated with enhanced fatty acid oxidation in rat liver (Ide et al 2009 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In red sea bream, both feeding conditions and dietary lipid and fatty acid levels were shown to alter lpl expression in liver, with lower expression in fish fed low lipid than in fish fed high lipid (Liang et al 2002a ). In the present study, the expression of lpl in liver of ABT juveniles was low and showed no clear response to diet, similar to previous studies where ABT larvae fed different live prey showed variable lpl expression (Betancor et al 2017a , b ). In contrast, hmgcl expression was upregulated in ABT juveniles fed higher lipid (20KO), while previous studies in larvae did not show any dietary regulation of this gene (Betancor et al 2017a , b ) although increased expression of this enzyme has been associated with enhanced fatty acid oxidation in rat liver (Ide et al 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the expression of lpl in liver of ABT juveniles was low and showed no clear response to diet, similar to previous studies where ABT larvae fed different live prey showed variable lpl expression (Betancor et al 2017a , b ). In contrast, hmgcl expression was upregulated in ABT juveniles fed higher lipid (20KO), while previous studies in larvae did not show any dietary regulation of this gene (Betancor et al 2017a , b ) although increased expression of this enzyme has been associated with enhanced fatty acid oxidation in rat liver (Ide et al 2009 ). Therefore, in the present study, the upregulation of hmgcl in fish fed the higher lipid content could be related to enhanced oxidation of lipids, consistent with the regulation of cpt1 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Taken together these results indicate a digestive promoting effect of taurine at an enrichment level of 3.7 mg taurine g -1 rotifer, which was entirely consistent with the impact of dietary taurine on ABT larval growth. However, it is worth noting that the expression levels of the digestive genes could be influenced by growth rather than dietary taurine levels, as previously suggested (Betancor et al, 2017b). Indeed, similar results were found by Saele et al (2010), where a relationship between bal genes and cod (Gadus morhua) larvae body size was shown.…”
Section: Discussionsupporting
confidence: 81%